2022
DOI: 10.3390/math10162915
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Time SeriesUsing an Automatic New Algorithm of the Kalman Filter

Abstract: Time series forecasting is one of the main venues followed by researchers in all areas. For this reason, we develop a new Kalman filter approach, which we call the alternative Kalman filter. The search conditions associated with the standard deviation of the time series determined by the alternative Kalman filter were suggested as a generalization that is supposed to improve the classical Kalman filter. We studied three different time series and found that in all three cases, the alternative Kalman filter is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…The Kalman filter has often been used to refine an ARIMA model by introducing a state-space system [29][30][31][32][33]. Despite the limited explicit references to the Kalman filter in the field of agri-food production [13], recent studies have utilized this technique for fitting predictive models within the horticultural sector [34].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kalman filter has often been used to refine an ARIMA model by introducing a state-space system [29][30][31][32][33]. Despite the limited explicit references to the Kalman filter in the field of agri-food production [13], recent studies have utilized this technique for fitting predictive models within the horticultural sector [34].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this study, we built on previous research [61,[94][95][96][97][98] to propose two hybrid forecasting models. The first model uses a novel approach of the Kalman filter [34] combined with a multilayer perceptron (MLP) neural network that has one hidden layer as its base architecture. The second model replaces NAR with SVR.…”
Section: Description Of the Hybrid Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we performed envelope extraction, extracting only the endpoints of the graph. After envelopment, the data were extracted and smoothed by applying the Kalman filter [20]. Comparing the data before and after smoothing, we found that the data before smoothing (Figure 6b) were more suitable for gait analysis and discrimination.…”
Section: Data Preprocessing For the Analysismentioning
confidence: 99%
“…Nonetheless, both the ARIMA and ARIMA-SVR models inherit limitations from the ARIMA framework, rendering them somewhat inflexible due to their reliance on linear relationships between observed variable values [28,29]. To overcome these limitations, the focus of autoregressive modeling has shifted towards neural networks in recent years [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%